Risk Management and Information Disclosure in Supply Chain Analysis - Ceravolo, Paolo; Cimato, Stelvio; Damiani, Ernesto; Gianini, Gabriela; Fugazza, Cristiano; Marrara, Stefiania (Advanced Information Technologies for Management – AITM 2008, 2008)
Supply Chain Management (SCM) has become an important issue in business modelling, with the aim of reducing the manufacturing cycle time, delivery lead-time, and inventory stocks. Traditional SCM technologies view supply chain risk as an explicit variable that can be accounted for, quantified, and optimized. However, managing risks related to the behaviour of supply chain participants requires some additional formalization to quantify the total risk associated to a particular configuration of the supply chain. Individual coalition participants can evaluate, computing a fairness function, to which extent the common good objective of the supply chain will keep them away from their individual objectives. In this paper we argue that if this distance is too great, individuals will adopt uncooperative behaviour to push the coalition back to a situation fairer to them, moving away from the common good. We propose a game-theoretical approach to evaluate a coalition's lack of balance and derive a risk assessment methodology out of it.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 38-46